2011
DOI: 10.1111/j.1467-9604.2010.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

The curriculum for children with severe and profound learning difficulties at Stephen Hawking School

Abstract: The increasing number of children with profound and multiple learning difficulties means that many schools for children with severe learning difficulties are having to review the curriculum that they offer. In addition, these schools are continuing to question whether a subject-based approach, in line with the National Curriculum, is the most appropriate way of meeting the educational needs of children working at the earliest stages of development. The staff at Stephen Hawking School, in east London, have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Further, there is the necessity for parents and carers of all children to feel that our education systems are ensuring that their children reach their full potential (Hodge & Runswick-Cole, 2008). Thus, measuring progress must be achieved using other methods (Rayner, 2011) and if the progress of these children cannot be measured on their academic performance, how are we to measure progress and what are we going to measure?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, there is the necessity for parents and carers of all children to feel that our education systems are ensuring that their children reach their full potential (Hodge & Runswick-Cole, 2008). Thus, measuring progress must be achieved using other methods (Rayner, 2011) and if the progress of these children cannot be measured on their academic performance, how are we to measure progress and what are we going to measure?…”
mentioning
confidence: 99%
“…Changes were made in that hospitals and institutionalised establishments were closed and children with ID taught in special schools using an adapted curriculum to fit the children's needs. The National Curriculum was first introduced as part of the Education Reform Act in 1988 along with National Curriculum assessments, but teachers found that it was totally unsuitable for children in special schools (Rayner, 2011). It was not until 1998 that Pre-National Curriculum Performance Scales (DfE 2014) or 'P Scales' (later called levels) were launched to assess students with intellectual disabilities working below the level of National Curriculum tests and assessments.…”
mentioning
confidence: 99%